Assessment of drug–drug interaction in an elderly human immunodeficiency virus population: Comparison of 3 expert databases. Issue 3 (4th August 2020) - Ruellan, Anne‐Lise; Bourneau‐Martin, Delphine; Joyau, Caroline; Secher, Solène; Fialaire, Pascale; Hitoto, Hikombo; Leautez, Sophie; Michau, Christophe; Vatan, Rémi; Billaud, Eric; Briet, Marie; Jolliet, Pascale; et al.
Abstract : Aims: Polypharmacy increase the risk of drug–drug interactions (DDIs) in the elderly population living with human immunodeficiency virus (HIV). Several expert databases can be used to evaluate DDIs. The aim of the study was to describe actual DDIs between antiretroviral drugs and comedications in an elderly population and to compare grading of the DDIs in 3 databases. Methods: All treatments of HIV‐infected subjects aged 65 years and older were collected in 6 French HIV centres. Summary of Product Characteristic (SPC), French DDI Thesaurus (THES), and Liverpool HIV DDI website (LIV) were used to define each DDI and specific grade. DDIs were classified in yellow flag interaction (undefined grade in SPC and THES or potential weak interaction in LIV), amber flag interaction (to be considered/precaution of use in SPC and THES and potential interaction in LIV) and red flag interaction (not recommended/contraindication in SPC and THES and do not administer/contraindication in LIV). Results: Among 239 subjects included, 60 (25.1%) had at least 1 DDI for a total of 126 DDIs: 23/126 red flag DDIs were identified in 17 patients. All these 23 DDIs were identified in LIV. THES and SPC missed 6 and 1 red flag DDIs, respectively. Seven of 23 red flag DDIs were identified in the 3 databases concomitantly. Conclusion: Polypharmacy is frequent in this elderly HIV population leading to DDI in a quarter of the subjects. The discrepancies between databases can be explained by differences in analysis methods. A consensus between databases would be helpful for clinicians.